The great smog of China a short event history of air pollution - Ahlers, Anna L. 1982-; Hansen, Mette Halskov 1962-; Svarverud, Rune (Association for Asian Studies, 2020)
Foul Air in Ancient China -- 1900-1949: China's Age of Smoke and Air Hygiene -- 1949-1978: The Ideologization of Smoke -- 1978-2008: The Diversification of Air Pollution Concerns -- 2008-2017: The Popularization of Air Pollution
Includes bibliographical references and index
Keywords: Air / Pollution / China / History